2008
DOI: 10.1007/s11240-008-9354-4
|View full text |Cite
|
Sign up to set email alerts
|

In vitro culture of Hibiscus rosa-sinensis L.: Influence of iron, calcium and BAP on establishment and multiplication

Abstract: Some factors influencing in vitro cultures of potted Hibiscus rosa-sinensis L. using nodal cuttings were investigated. A protocol using a modified MS medium helped to overcome chlorosis, shoot tip necrosis (STN) and leaf drop. These disorders have been caused by mineral imbalance associated with calcium and iron deficiency. STN and leaf drop were overcome by increasing calcium level from 3 mM (MS standard concentration) to 9 mM, and this increase, in addition, enhanced shoot dry weight and shoot extension. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
32
0
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(35 citation statements)
references
References 26 publications
(35 reference statements)
2
32
0
1
Order By: Relevance
“…In this case, plant tissue culture techniques may be able to facilitate the large-scale production of valuable clones to avoid further depletion of this species from its natural habitat (Conde et al, 2008). Significant features of in vitro propagation are the enormous multiplication capacity in a relatively short time span, the production of healthy and disease-free plants, and the ability to generate propagules throughout the year independent of seasonal changes (Christensen and Sriskandarajah, 2008). Additionally, it is also a useful method to propagate endangered plant species with the purpose of optimizing the time and cost required to aid in preservation (Christensen and Sriskandarajah, 2008).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this case, plant tissue culture techniques may be able to facilitate the large-scale production of valuable clones to avoid further depletion of this species from its natural habitat (Conde et al, 2008). Significant features of in vitro propagation are the enormous multiplication capacity in a relatively short time span, the production of healthy and disease-free plants, and the ability to generate propagules throughout the year independent of seasonal changes (Christensen and Sriskandarajah, 2008). Additionally, it is also a useful method to propagate endangered plant species with the purpose of optimizing the time and cost required to aid in preservation (Christensen and Sriskandarajah, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…Significant features of in vitro propagation are the enormous multiplication capacity in a relatively short time span, the production of healthy and disease-free plants, and the ability to generate propagules throughout the year independent of seasonal changes (Christensen and Sriskandarajah, 2008). Additionally, it is also a useful method to propagate endangered plant species with the purpose of optimizing the time and cost required to aid in preservation (Christensen and Sriskandarajah, 2008). In view of the importance and advantages of plant tissue culture, this study aimed to determine the effects of supplementation of various plant growth regulators (PGRs) on in vitro leaf and stem explants of L. pumila.…”
Section: Introductionmentioning
confidence: 99%
“…The decrease of leaf chlorophyll content in in vitro grown plants can limit the photosynthetic rate by reducing light absorption (CHRISTENSEN et al, 2008). In this study, for fresh weight, chlorophyll a, chlorophyll b, and carotenoids, the flasks with two membranes were superior to the others; although the treatment with one membrane was more efficient in increasing these characteristics than the treatment without membrane (Table 1).…”
Section: Resultsmentioning
confidence: 57%
“…Due to the strikingly encouraging effects of plant growth regulator (PGR) in accelerating, inducing, and maintaining in vitro shoots, direct in vitro shoots establishment and multiplication from explants often involve the application of PGRs such as 6-benzylaminopurine (BAP) [12,13], zeatin [14], BAP plus kinetin (KIN) [15], BAP plus indole-3-acetic acid (IAA) [16], or BAP plus naphthalene-3-acetic acid (NAA) [17]. Christensen et al [13]) reported that the most suitable multiplication medium for H. rosa-sinensis L. was demonstrated to be a modified Murashige and Skoog (MS) medium containing 2.2 μM BAP and increased concentrations of calcium at 9 mM and iron at 295 μM provided as ethylenediamine di-2-hydroxyphenyl acetate ferric (Fe-EDDHA).…”
Section: Introductionmentioning
confidence: 99%
“…Christensen et al [13]) reported that the most suitable multiplication medium for H. rosa-sinensis L. was demonstrated to be a modified Murashige and Skoog (MS) medium containing 2.2 μM BAP and increased concentrations of calcium at 9 mM and iron at 295 μM provided as ethylenediamine di-2-hydroxyphenyl acetate ferric (Fe-EDDHA). Bhalla et al [18] modified the MS medium strength coupled with BAP in inducing direct shooting from H. rosa-sinensis but concluded that BAP was not suitable in their study.…”
Section: Introductionmentioning
confidence: 99%